Underpricing of Initial Public Offering (IPO) in China - GU, XINYUAN (2014)
This paper studies the issue of initial public offerings (IPO) underpricing on Chinese A-share market using the sample of 838 IPO shares from 2002 to 2014 excluding 2013. The research reviews some classic western theories and hypotheses as well as studies carried by Chinese scholars which shows the difference of IPO underpricing between Chinese stock market and other stock markets. Based on these literature, a multiple regression model is constructed to test the influential factors of IPO underpricing in Chinese stock market. From the regression result, 3 main reason of the high IPO underpricing level in China can be concluded. The first cause is the problem of informational asymmetry which is owing to the immature IPO regulation, therefore the disclosure of information is not efficient. The second factor is the irrational investment behaviour in Chinese market. It confirms the phenomenon of severe speculation in secondary market. Thirdly, the result of variables that used to represent the special features of Chinese stock market shows that the high inequity of demand and supply in Chinese stock market still exists after the reform of IPO system and it is a main reason of IPO underpricing in China.